Comparative Gut Microbiome in Trachypithecus leucocephalus and Other Primates in Guangxi, China, Based on Metagenome Sequencing - Que, Tengcheng; Pang, Xianwu; Huang, Hongli; Chen, Panyu; Wei, Yinfeng; Hua, Yiming; Liao, Hongjun; Wu, Jianbao; Li, Shousheng; Wu, Aiqiong; He, Meihong; Ruan, Xiangdong; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The Trachypithecus leucocephalus (white-headed langur) is a highly endangered, karst-endemic primate species, inhabiting the karst limestone forest in Guangxi, Southwest China. How white-headed langurs adapted to karst limestone and special dietary remains unclear. It is the first time to study the correlation between the gut microbiome of primates and special dietary, and environment in Guangxi. In the study, 150 fecal samples are collected from nine primates in Guangxi, China. Metagenomic sequencing is used to analyze and compare the gut microbiome composition and diversity between white-headed langurs and other primates. Our results indicate that white-headed langurs has a higher diversity of microbiome than other primates, and the key microbiome are phylum Firmicutes, class Clostridia, family Lachnospiraceae, and genera Clostridiates and Ruminococcus, which are related to the digestion and degradation of cellulose. Ten genera are significantly more abundant in white-headed langurs and François’ langur than in other primates, most of which are high-temperature microbiome. Functional analysis reveals that energy synthesis-related pathways and sugar metabolism-related pathways are less abundant in white-headed langurs and François’ langur than in other primates. This phenomenon could be an adaptation mechanism of leaf-eating primates to low-energy diet. The gut microbiome of white-headed langurs is related to diet and karst limestone environment. This study could serve as a reference to design conservation breeding, manage conservation units, and determine conservation priorities.